Enhancing job application writing: A comparative case study of AI and human feedback on grammar and mechanics - Noerjaman, Lutfi Arief; Dallyono, Ruswan; Hidayati, Farida (UPT Bahasa Universitas Tanjungpura, 2025)
Submission of well-structured job application letters is an essential aspect of business and government recruitment processes. However, due to difficulties with grammar and mechanics, many students, fresh graduates included, fail to produce high-quality job applications. While human reviewers typically give feedback to enhance these skills, Artificial Intelligence (AI) has brought about automated feedback systems. The research compared the performance of two artificial intelligence models, Gemini and ChatGPT, and human experts in assessing job application letters. The study compared feedback in six writing features